Avaliação imuno-histoquímica de micrometástases linfonodais no câncer de colo do útero em estádios iniciais e correlação com recidiva tumoral - Leandro Freitas, Colturato, (2016)
Introduction: Ten to 15% of cervical cancer patients have had tumor recurrence in early stage (FIGO IB1 - IIA). They have presented negative lymph nodes to hematoxylin-eosin (HE) staining technique. Objectives: In patients with cervical cancer in stage IB1 - IIA (FIGO): 1) to assess the prevalence of pelvic lymph node micrometastasis (MI) through the immunoreactivity of antibody anti pan - cytokeratin AE1/AE3 in lymph node tissue and its correlation with tumor recurrence and overall survival; 2) to describe, in the primary tumor of patients with recurrence tumor and/or lymph node micrometastasis, the immunohistochemical expression (IHC) of the lymphatic endothelial marker D2-40 and their correlation with histopathologic findings by conventional hematoxylin-eosin staining. Material and Method: We studied 83 medical records of patients admitted at Centro de Referência da Saúde da Mulher do Estado de São Paulo (Hospital Pérola Byington) in clinical stages IB1, IB2, and IIA. They were submitted exclusively to primary surgical treatment with hysterectomy Querleu C1 and had no lymph node metastases in the presence of Hematoxylin-Eosin. We collected data from the patients’ medical records. We studied variables, such as sociodemographic, reproductive, and histopathological characteristics, as well as the therapeutic follow-up of these patients. The histological sections of the tumors were reviewed systematically. Each lymph node was analyzed by IHC with AE1/AE3 antibody with six histological sections of three micrometers thick. The patients were divided into groups with recurrence (GCR) and without recurrence (GSR). The patients were also separated according to the presence or absence of lymph node micrometastasis or isolated tumor cells. Qualitative and quantitative variables between groups were compared using chi-square test and parametric Student's t-test. Results: Fifteen patients (18.07%) have had recurrence. At a significance level of 5%, there was significant difference between the GCR and GSR and the variables: pregnancies, size of the major axis of the tumor (cm), lymph node micrometastasis, clinical stage IB2 or IIA, and the mean number of negative lymph nodes. The direct analysis with lymph node micrometastasis or isolated tumor cells showed a significant difference among the variables clinical stage IB2 or IIA, and a stromal invasion depth greater than 2/3. Conclusions: The presence of lymph node micrometastasis is an important risk factor to tumor recurrence. These patients should be considered eligible for radiochemotherapy adjuvant treatment.